2022
DOI: 10.1039/d2ay00331g
|View full text |Cite
|
Sign up to set email alerts
|

Application of a novel hydroxyl functionalized fluorescent covalent organic framework for turn-off ultrasensitive Zn2+ ion detection

Abstract: In this research, a novel hydroxyl functionalized covalent organic framework (COF) with fluorescent properties was rationally designed based on the reaction between 2,5-dihydroxy-terephthalic-dihydrazide (DHTPz) and 1,3,5-benzenetricarboxaldehyde (Bt) for the Zn2+...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Examining its luminescence and quenching in different solvents, it is observed that GC-TFPB-AO shows peak fluorescence emission at 400–600 nm when irradiated at 370 nm, with the most significant degree of fluorescence quenching observed in polar DMF (Figures a and S5). Therefore, we chose DMF as the dispersant in further experiments. The sensitivity of GC-TFPB-AO toward UO 2 2+ was further improved by modification with an AO group (Figure S6).…”
Section: Resultsmentioning
confidence: 99%
“…Examining its luminescence and quenching in different solvents, it is observed that GC-TFPB-AO shows peak fluorescence emission at 400–600 nm when irradiated at 370 nm, with the most significant degree of fluorescence quenching observed in polar DMF (Figures a and S5). Therefore, we chose DMF as the dispersant in further experiments. The sensitivity of GC-TFPB-AO toward UO 2 2+ was further improved by modification with an AO group (Figure S6).…”
Section: Resultsmentioning
confidence: 99%
“…The size increase may be attributed to the coordination between encapsulated payloads and Zn 2+ ions . It has been reported that Zn 2+ can not only coordinate with nitrogen atoms in the quinoline/pyrazoles structure of BAY-876 and CQ but also form a stable complex with the oxygen atoms in hydroxyl groups of 2-DG. Therefore, BAY-876, CQ, and 2-DG will participate in the formation of ZIF-8, resulting in a larger particle size. The Fourier-transform infrared spectroscopy (FT-IR) spectrum of D/B/CQ@ZIF-8@CS displayed the strong absorption peak corresponding to the stretching vibration of C–O bond in the sugar ring of CS (1061 cm –1 ) (Figure g).…”
mentioning
confidence: 99%